2020
DOI: 10.1111/are.14759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on the ions important and sodium‐potassium ATPase in osmoregulation, cortisol, amino acids, digestive and immune enzymes in Scylla paramamosain during indoor overwintering

Abstract: Overwintering is an important part of the conservation of Scylla paramamosain, and salinity has an important effect on the conservation of S. paramamosain during overwintering. Three salinities (4‰, 12‰ and 25‰) were selected as the overwintering salinities to reveal the effects of different salinities on the relevant important ions in osmotic pressure regulation, plasma cortisol, digestive enzymes, immune enzymes and amino acids of S. paramamosain during indoor overwintering. Results indicated that after over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The hierarchical clustering heat maps of DEGs for LS and HS groups are shown in Figure 1c. It is well‐known that metabolism plays an important role in salinity during overwintering in S. paramamosain (Zhou, Li, Wang, Mu, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hierarchical clustering heat maps of DEGs for LS and HS groups are shown in Figure 1c. It is well‐known that metabolism plays an important role in salinity during overwintering in S. paramamosain (Zhou, Li, Wang, Mu, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids play an important role in the metabolism of crustaceans, and they are particularly important for the adaptation to different salinities (Zhou, Li, Wang, Mu, et al, 2020). Amino acid metabolism determines oxidization through the Krebs cycle in order to produce carbon dioxide and water, and release energy (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,41 Interestingly, specific amino acids such as Met, Trp, Val, Ile, and Leu exhibit significant positive correlations with salinity, suggesting their unique biochemical functions in combating salinity stress. 47,48 In the correlation analysis of free nucleotides, it was observed that a majority of them exhibited a positive correlation with salinity, suggesting an influence of salinity on the nucleotide levels. Notably, our study identified a general positive correlation between free amino acids and nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that salinity is one of the most important environmental factors affecting aquatic animals (Sara et al, 2010; Zhang et al, 2016). Previous studies have focused on survival and growth (Pan et al, 2007; Romano & Zeng, 2006), osmotic regulation (Lu et al, 2019; Zhou, Li, Wang, Mu, et al, 2020), behaviour (Re et al, 2006; Shentu et al, 2015), gene expression (Hu et al, 2015; Zhao et al, 2015) and physiological levels (Anger et al, 2008; Bianchini et al, 2008). Additionally, metabolism has been shown to be affected by salinity (Santos et al, 2014; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%